Straw mulching-driven microbial relay enhances soil C–N coupling and cotton yield–quality synergy - Xie, Zhangshu; Qin, Yeling; Xie, Xiaodong; Li, Jiarui; Zheng, Lijuan; Jiang, Youhong; Tu, Xiaoju; Liu, Aiyu; Zhou, Zhonghua (Frontiers in Plant Science, 2025)
IntroductionStraw return is a widely endorsed sustainable agronomic practice. However, a systematic understanding of its carbon–nitrogen coupling mechanisms and their consequent impacts on the soil–microbe–plant continuum across the entire cotton growth cycle is critically lacking.MethodsWe conducted a field experiment with five treatments: CK (no straw return), T1 (one-third shredded straw), T2 (two-thirds shredded straw), T3 (full shredded straw), and T4 (full straw left intact as surface mulch). This design enabled us to decipher how the amount and fragmentation of straw residues synchronize the soil-microbe-plant system to enhance sustainability.ResultsOur findings reveal distinct mechanistic pathways. The T3 treatment (full shredding) triggered an early-season microbial "relay," where Gammaproteobacteria expansion was succeeded by Actinobacteria, elevating soil pH from 4.82 to 5.73 and boosting alkaline-hydrolysable N by 113.01% at the flower and boll stage. This enhanced nitrate reductase activity by 74.1% and increased bolls per plant by 35.0%. In contrast, the T4 treatment (surface mulch) provided a more gradual nitrogen release (+28.4% alkaline-hydrolysable N during boll opening), which prolonged the secondary cell wall deposition phase in fibers. This strategy achieved a lint yield of 2055.63 kg ha⁻¹ (+63.8%) and a 2.6% increase in fiber strength. Furthermore, T4 fostered a "microbial sanctuary" at boll opening, evidenced by a 130.5% explosion in OTU richness and an 18.7% suppression of pathogen populations.DiscussionWe demonstrate that surface mulching (T4) is the superior strategy, as it optimally balances high yield with superior fiber quality by creating a resilient and suppressive soil microbiome. This work provides a novel carbon–nitrogen synergy framework for the resource-efficient utilization of crop residues in sustainable cotton production.